PRAGMATIC EFFECTS IN SLANGS AND CATCHY PHRASES IN SELECTED SONGS OF WIZKID - ISHAYA, Yusuf Tsojon (International Journal of Arts, Languages, Linguistics and Literary Studies, 2023)
Slang forms and catchy phrases give linguistic aesthetics to songs and most significantly, they allow singers to pass lots of messages, even while they utter just few of those messages. This suggests that there are hidden messages in slang forms and catchy phrases utilized in hip-hop songs, and for these hidden messages to be known to listeners, a specific level of language analysis has got to be put in situ. This study therefore, set out to undertake a pragmatic analysis of slang and catchy phrases utilized in some selected Wizkid’s hip-hop songs, the songs are; “Bombay” (2014), “Sound it” (2014), “Wad Up” (2011), “On Top Your Matter” (2011) and “Joro” (2019). The target of this study is to spot the important meanings of slang forms and catchy phrases that are utilized in Nigerian hip-hop songs, with regard to the general meanings of those songs themselves. This identification will successively help us to state the explanations why they (these slang forms and catchy phrases) are utilized in the songs of Wizkid and their contributions to the singer’s intended meanings of those songs.